Die Sammlung Paul Maenz : Neues Museum Weimar - Band 1 Objekte - Bilder - Installationen - Bothe, Rolf; Dickel, Hans; Maenz, Paul; Wendermann, Gerda; Neues Museum, Weimar; Kunstsammlungen zu Weimar, Weimar (Ostfildern-Ruit : Cantz Verlag, 1998)
Andre, Carl ; Anselmo, Giovanni ; Armleder, John ; Art & Language ; Barry, Robert ; Bömmels, Peter ; Boetti, Alighiero ; Bonvicini, Monica ; Büttner, Werner ; Bulloch, Angela ; Buren, Daniel ; Burgin, Victor ; Chia, Sandro ; Clemente, Francesco ; Dahn, Walter ; Darboven, Hanne ; de Dominicis, Gino ; De Maria, Nicola ; Disler, Martin ; Dokoupil, Jiri Georg ; Endart ; Fabro, Luciano ; Feldmann, Hans-Peter ; Fetting, Rainer ; Riverhead (New York) ; Fleury, Sylvie ; Haring, Keith ; Judd, Donald ; Kawara, On ; Kiefer, Anselm ; Knoebel, Imi ; Kosuth, Joseph ; LeWitt, Sol ; Long, Richard ; Manzoni, Piero ; Oehlen, Markus ; Opie, Julian ; Paladino, Mimmo ; Paolini, Giulio ; Penone, Giuseppe ; Rockenschaub, Gerwald ; Roehr, Peter ; Ruff, Thomas ; Salvo ; Scholte, Rob ; Schütte, Thomas ; Schulze, Andreas ; Schuyff, Peter ; Sturtevant, Elaine ; Taaffe, Philip ; Toroni, Niele
Duits
boek